2007
DOI: 10.1590/s1807-59322007000300016
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Information on Varicella History in Preschool Children

Abstract: ER. Reliability of information on varicella history in preschool children. Clinics. 2007;62(3):309-14. OBJECTIVE:To verify how reliable is the information provided by parents about the history of varicella in their children. METHODS: 204 parents of previously healthy children attending two municipal day-care centers of São Paulo city were interviewed between August 2003 and September 2005. A standardized form was filled out with information regarding age, sex, history of varicella and other diseases, drug use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…[15] Varicella is a highly contagious disease, particularly after the close contact as household contact or in collection environments such as day care centers. [16] In our locality, the life pattern of large families sharing same house, play a role in increasing the incidence of VZV infection among the urban areas. This results is consistent with a study done in Turkey which reported that varicella seropositivity was higher in large families with five or more members (91.2%) than small families with four or fewer members (80%).…”
Section: Discussionmentioning
confidence: 95%
“…[15] Varicella is a highly contagious disease, particularly after the close contact as household contact or in collection environments such as day care centers. [16] In our locality, the life pattern of large families sharing same house, play a role in increasing the incidence of VZV infection among the urban areas. This results is consistent with a study done in Turkey which reported that varicella seropositivity was higher in large families with five or more members (91.2%) than small families with four or fewer members (80%).…”
Section: Discussionmentioning
confidence: 95%
“…Classification bias is unlikely, as true subclinical varicella is rare and clinical diagnosis easy in children presenting lesions [20]. Recall bias should also be limited, given the large positive predictive and negative predictive values of varicella history for school-aged children (95 % and 90 %, respectively) [21][22][23]. Furthermore, our estimates of cumulative incidence of varicella at age 11 years are similar to that of a recent independent French seroprevalence study (90 % at age 11 years [24]) as well as earlier figures in France [25].…”
Section: Discussionmentioning
confidence: 99%
“…This assumption was based on very high positive predictive values reported in a number of seroprevalence studies. [10][11][12][13][14][15][16][17][18] All students with a negative history of chicken pox were invited for serological testing. Those who volunteered for the test were given a full explanation of the study and written informed consent was obtained.…”
Section: Methodsmentioning
confidence: 99%